2013
DOI: 10.1007/s11434-013-5983-z
|View full text |Cite
|
Sign up to set email alerts
|

The third family of compact stars with the color-flavor locked quark core

Abstract: In this paper, we study the third family of compact stars with the color-flavor locked (CFL) quark core. The relativistic mean field model is used for hadronic matter and the MIT bag model for CFL quark matter. The results of the calculation show a transitional behavior that goes from the hadron star range, through the transition range, into the CFL quark star range. In the transition range, the third family of compact stars with the CFL quark matter core is found in the wide range of the CFL energy gap 100 Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Respectively, the SQM sphere contains 1.37×10 9 u-quarks, 1.48 × 10 9 d-quarks, 1.26 × 10 9 s-quarks, and 2.74 × 10 5 electrons, which gives the total core charge Q(R) = 2.66 × MeV. It is worth mentioning that if B exceeds the upper bound, SQM is unstable and may only exist at the core of a compact star, i.e., hybrid star [13,57].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Respectively, the SQM sphere contains 1.37×10 9 u-quarks, 1.48 × 10 9 d-quarks, 1.26 × 10 9 s-quarks, and 2.74 × 10 5 electrons, which gives the total core charge Q(R) = 2.66 × MeV. It is worth mentioning that if B exceeds the upper bound, SQM is unstable and may only exist at the core of a compact star, i.e., hybrid star [13,57].…”
Section: Resultsmentioning
confidence: 99%
“…We take the three typical values B 1/4 = 145, 152, and 159 MeV. It is worth mentioning that if B exceeds the upper bound, SQM is unstable and may only exist at the core of a compact star, i.e., hybrid star [13,57].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, we obtain twin star configurations and special points (SPs) on the M − R diagram with all the considered hadronic models. Several works have suggested that phase transition from hadronic to unpaired or color-flavor locked quark matter often leads to the formation of a "third family" of compact stars [8,17,27,55,[62][63][64][65][66][67][68][69][70][71][72] and twin star configurations under certain circumstances of strong first order phase transitions mainly with considerable density jumps. The M −R plot in such cases often show non-identical branches with two distinct maxima at two different radii.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [72] studied smooth phase transition with Gibbs construction and obtained SPs on the mass-radius diagram for different values of the bag constant. In the present work with the considered number of hadronic models and for different values of B as for density-dependent bag model, we have achieved phase transition with Maxwell construction and analyzed the properties of HSs.…”
Section: Introductionmentioning
confidence: 99%